2014
DOI: 10.1051/0004-6361/201423507
|View full text |Cite
|
Sign up to set email alerts
|

Suite of hydrodynamical simulations for the Lyman-αforest with massive neutrinos

Abstract: The signature left in quasar spectra by neutral hydrogen in the Universe allows constraining the sum of the neutrino masses with a better sensitivity than laboratory experiments and may shed new light on the neutrino mass hierarchy and the absolute mass-scale of neutrinos. Constraints on cosmological parameters and on the dark energy equation of state can also be derived from a joint parameter estimation procedure. However, this requires a detailed modeling of the line-of-sight power spectrum of the transmitte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 152 publications
1
69
0
Order By: Relevance
“…[39] and [40] and also affects the prediction for the primordial abundance of light elements, see for example [41]. Rossi et al [42] recently presented constraints from Lyman-α forest measurements in conjunction with a variety of probes.…”
Section: B Gravitational Wave Contribution To the Massless Degrees Omentioning
confidence: 99%
“…[39] and [40] and also affects the prediction for the primordial abundance of light elements, see for example [41]. Rossi et al [42] recently presented constraints from Lyman-α forest measurements in conjunction with a variety of probes.…”
Section: B Gravitational Wave Contribution To the Massless Degrees Omentioning
confidence: 99%
“…Massive neutrinos have also an impact on the halo mass function, as the same authors have shown that in massive neutrino cosmologies this constraint can be entirely, and universally, described in terms of the properties of the CDM field alone (see also Brandbyge et al 2010, where this aspect has been suggested for the first time). Additional signatures of the presence of a massive neutrino background are also expected on the Ly-α forest Viel et al (2010); Villaescusa-Navarro et al (2013); Rossi et al (2014), on the Sunyaev-Zeldovich and X-ray properties of galaxy clusters (Roncarelli et al 2014), on the redshift-space distortions Marulli et al (2011), and on the cosmic voids statistics Villaescusa-Navarro et al (2013).…”
Section: Massive Neutrino Cosmologiesmentioning
confidence: 95%
“…However, as we only wish to estimate the magnitude of the impact of modified-gravity theories, for simplicity we keep the analytical model (4.4). For precise measurements, one should in any case develop dedicated hydrodynamical simulations [44,53,54].…”
Section: )mentioning
confidence: 99%